2019
DOI: 10.1155/2019/5856405
|View full text |Cite
|
Sign up to set email alerts
|

Second Mesiobuccal Canal Evaluation Features with Cone-Beam Computed Tomography

Abstract: Aim. The aim of the study is to evaluate the difference in MB2 prevalence with different slice thicknesses in maxillary first molars. Materials and Methods. Two hundred nonfilled MB2 canals in maxillary first molars of 156 people (75 females and 81 males) aged from 20 to 73 years old were evaluated with CBCT with different slice thicknesses: 0.5 mm, 1 mm, 3 mm, and 10 mm. A general analysis was performed out, as well as in the age groups and on gender groups. Results. Visualization with 0.5 mm and 1 mm slice t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…However, several studies demonstrated different conclusions on the dependence of the slice thickness of CBCT scans and the detection of the anatomical and other structures, as well as the way that reduces artefacts [18][19][20][21][22][23][24]. Our choice of slice thickness was 1 mm for good and moderate detection of CS without missing it and with high reduction of artefacts in this case.…”
Section: Discussionmentioning
confidence: 82%
“…However, several studies demonstrated different conclusions on the dependence of the slice thickness of CBCT scans and the detection of the anatomical and other structures, as well as the way that reduces artefacts [18][19][20][21][22][23][24]. Our choice of slice thickness was 1 mm for good and moderate detection of CS without missing it and with high reduction of artefacts in this case.…”
Section: Discussionmentioning
confidence: 82%
“…15 Additionally, Mordanov et al conducted a study in Russian patients and stated that no significant correlation could be found between sex, age, and race and the prevalence of MB2 canal. 31 Using an operating microscope, Das et al discerned no significant difference in the prevalence rate of MB2 canal according to age, sex, or side. 32 Falcão et al also reported no significant differences in the existence of MB2 canal according to age and sex.…”
Section: Discussionmentioning
confidence: 99%
“…el uso de este software promete ser un avance significativo en la endodoncia moderna, minimizando errores en la práctica clínica en cuyos casos la anatomía radicular presenta cierta complejidad. 6,15,[20][21][22][23][24][25][27][28][29][30][31][32][33][34][35][36] El no encontrar diferencia significativa en los resultados puede ser una muestra de cierto grado de simetría anatómica entre los conductos mesiovestibular y mesiolingual, aunque eso no significa que existan casos donde las variantes anatómicas entre ellos sean mayores; esto puede tener correlación con estudios de caracterización morfológica donde se ha observado simetría bilateral en la morfología oclusal de molares inferiores. 37…”
Section: Wwwmedigraphicorgmxunclassified